837 Narcolepsy in a toddler. (3rd May 2021) - Sekhon, Anupamjeet; Prero, Moshe; Ross, Kristie; Ibrahim, Sally
Abstract: Introduction: Narcolepsy is a central disorder of hypersomnia with a bimodal peak incidence at ages 15 and 35. Onset in early childhood has been reported, but rarely under the age of 5. We present a case of Narcolepsy Type 1 in a 2.5-year-old with dropping spells. Report of case(s): A 2.5-year-old African American healthy male presented with acute onset sudden drops, unsteady gait, and staring spells. These episodes lasted a few seconds, occurred multiple times a day, and were associated with eye fluttering and dysarthric speech. History was notable for increased daytime sleep/sleep attacks, disrupted nocturnal sleep with confusional arousals, nightmares and sleepwalking, weight gain and mood instability with aggressive behavior. No preceding head injury or illness. Physical examination demonstrated frequent atonic episodes with loss of deep tendon reflexes. A clinical suspicion of myoclonic/atonic epilepsy prompted video- electroencephalogram (EEG) which showed frequent bursts of generalized intermittent slowing representative of NREM 1 sleep lasting several seconds. Magnetic resonance imaging of the brain and infectious workup was unremarkable. Cerebrospinal fluid (CSF) Orexin was <50 pg/mL. While 76–98% of patients with narcolepsy type-1 have HLADQB1*06:02, our patient tested negative. Due to lack of MSLT validity at this age, only diagnostic PSG was performed which showed REM without atonia and sleep fragmentation. Prior to sleep onset, cataplexy was observed in the patient while laughing, though EMG tone was relatively preserved during this episode. We had limited treatment options considering lack of FDA approved medications for ages less than 7. A helmet was prescribed to prevent head injury. Methylphenidate 5mg/day improved sleepiness and slightly stabilized mood. For cataplexy, neither Fluoxetine nor Imipramine helped. His mother disapproved further medication trials. Continuing methylphenidate, the family was referred to behavior psychology for support, coping with the diagnosis and behavioral changes. Conclusion: This case demonstrates an unusual presentation of Narcolepsy Type 1 in a toddler initially thought to have epilepsy. Video-EEG and low CSF orexin led to the diagnosis. His age, severity of cataplexy, mood changes, and parental concerns made treatment challenging. Furthermore, this case highlights the importance of early recognition of Narcolepsy in young children to provide appropriate treatment during critical developmental stages. Support (if any):